2020
DOI: 10.1002/adma.202004930
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial Growth of Single‐Phase 1T'‐WSe2 Monolayer with Assistance of Enhanced Interface Interaction

Abstract: The WSe2 monolayer in 1T’ phase is reported to be a large‐gap quantum spin Hall insulator, but is thermodynamically metastable and so far the fabricated samples have always been in the mixed phase of 1T’ and 2H, which has become a bottleneck for further exploration and potential applications of the nontrivial topological properties. Based on first‐principle calculations in this work, it is found that the 1T’ phase could be more stable than 2H phase with enhanced interface interactions. Inspired by this discove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…The epitaxial 1T′-MoTe 2 films usually contain a majority of 2H-MoTe 2 domains because of the near degenerate energies of 1T′ and 2H phases of MoTe 2 . [42,43,60] Previous studies have indicated that, the strain control [25,49,51] and external electrical fields [50] were beneficial for the formation of 1T′-MoTe 2 .…”
Section: Phase Structure Of 1t′-mote 2 /Bi 2 Te 3 Vdwhmentioning
confidence: 99%
See 1 more Smart Citation
“…The epitaxial 1T′-MoTe 2 films usually contain a majority of 2H-MoTe 2 domains because of the near degenerate energies of 1T′ and 2H phases of MoTe 2 . [42,43,60] Previous studies have indicated that, the strain control [25,49,51] and external electrical fields [50] were beneficial for the formation of 1T′-MoTe 2 .…”
Section: Phase Structure Of 1t′-mote 2 /Bi 2 Te 3 Vdwhmentioning
confidence: 99%
“…[11,22,[41][42][43] Thus, of equal importance is their synthesis that always requires supporting substrates to stabilize the 1T′ structure. [25,44,45] As the sake of the fabrication of QSH-based devices, it is highly desirable to realize stable 1T′-MX 2 MLs with positive global band gaps by binding with suitable substrates and utilizing the proximity effects in their heterostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Strain is one of the most important approaches to tune the electronic properties of 2D materials. Experimental results prove the strain can induce metal-insulator transition and enhance the metastable phase growth [29,43]. In this section, we introduce the strained TB model based on the I-TB model.…”
Section: Strained Tb Modelmentioning
confidence: 99%
“…* liuj@ust.hk In addition to the extensive studies of WTe 2 , the exploration has also been extended to other related materials. For example, monolayer 1T'-WSe 2 [27][28][29] , 1T'-MoSe 2 [30], 1T'-MoTe 2 [31] and 1T'-MoS 2 [32] are successfully fabricated; plus WSe 2 and MoS 2 show a gapped bulk and conducting edge states in experiments. Observations of topological Fermi arcs [33] and superconductivity [34] in bulk MoTe 2 are also reported.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the 2D materials over the oxide surface facilitate direct device fabrication 35,36 . However, the fabrication process of monolayer WSe 2 film is yet sophisticated compared with other TMDCs 37 …”
Section: Introductionmentioning
confidence: 99%